The Role Of Artificial Intelligence In Personalized And Customized Engagement Marketing: A Comprehensive Review - Rolando, Benediktus (PT. Maju Malaqbi Makkarana, 2024)
Artificial intelligence is likely to have a significant impact on marketing strategies and customer behaviors in the years ahead. Research in this field has grown considerably, demonstrating AI's ability to simulate human behavior and perform tasks intelligently. With growing interest among marketing researchers and practitioners, this research aims to provide an overview of the evolution of both marketing and AI research fields. This paper explores the emerging role of artificial intelligence in personalized engagement marketing, which focuses on creating, communicating, and delivering customized offerings to customers. Utilizing the Systematic Literature Review technique, we examined over 300 academic articles to uncover prevalent themes and gain a deeper understanding of current AI utilization in marketing. We then propose a plan for future research that examines potential changes in marketing strategies and customer behaviors while emphasizing critical policy considerations related to privacy, bias, and ethics. The implications for marketing managers are discussed along with predictions about how AI will impact branding and customer management practices going forward. Our research highlighted several benefits of integrating AI into marketing such as improved customer interactions, increased revenue, reduced expenses, and enhanced overall efficiency. However, this research also pointed out areas requiring further investigation including challenges posed by AI integration like shortage of skilled personnel and data privacy concerns.